CONCEPTION RATE PADA SAPI PERAH LAKTASI DI BALAI BESAR PEMBIBITAN TERNAK UNGGUL DAN HIJAUAN PAKAN TERNAK BATURRADEN PURWOKERTO JAWA TENGAH - Fandi Abdillah; Madi Hartono; Siswanto . (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The aim of this research was to determine the level of CR and the factors value that affect the level of CR at lactating dairy cattle in BBPTU-HPT Baturraden Purwokerto Central Java, on April, 29 th – May 13 th 2014. This research used sensus method with primary and secondary data. Analysis data used regression analysis with SPSS (Statistics Packet for Social Science) program.The result showed that the CR at BBPTU-HPT Baturraden is 36,60%. Factors affecting the value of CR were the herds man and the cattles. On the level of cattle are the education of herds man that negatively associated with factor value 2,130, number of the cattle that negatively assosiated with factor value 0,151, herdsman knowledge that negatively assosiated with factor value 2,637, thawing duration that negatively associated with factor value0,229 and the distance between the cowshed with office that possitively assosiated with factor value 0,198. Factor affecting the CR on dairy cattle are the age dairy cattle that negatively associated with factor value 0,313, days open that possitively with factor value 0,725, mating postpartus that negatively associated with factor value 0,661, calving interval that positively associated with factor value 0,950, lactating period that possitively associated with factor value 0,923 and dry period that negatively associated with factor value 0,966.